(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Background: Maternal diabetes, including gestational diabetes mellitus (GDM) and pregestational diabetes, is a major determinant of neonatal complications. Aim:This study aimed to evaluate the immediate complications in infants of diabetic mothers (IDM).Materials and Method: A hospital-based observational study was conducted at the Department of Pediatrics, Medical College for Women and Hospital, from July 2024 to July 2025. A total of 120 neonates born to mothers with GDM or pregestational diabetes were included. Data on maternal diabetes type, glycemic control, mode of delivery, neonatal birth weight, clinical presentation, and complications—such as hypoglycemia, hyperbilirubinemia, hypocalcemia, respiratory distress, and polycythemia—were collected. Statistical analysis was performed using SPSS 26.Results: Of the 120 neonates, 54.17% were male. Most mothers had GDM (70.83%) and good glycemic control (HbA1c <6.5% in 47.5%). Preterm births comprised 27.5%. Respiratory distress was the most frequent complication (40%), followed by hypoglycemia (23.33%), hyperbilirubinemia (18.33%), and hypocalcemia (12.5%). Most neonates were appropriate for gestational age (63.33%), while 25.83% were large for gestational age (LGA) and 10.83% small for gestational age (SGA). No congenital anomalies or neonatal deaths were observed. The majority of neonates (92.5%) were discharged in good health, while 4.17% left against medical advice (LAMA). Immediate complications were slightly more common in neonates of pregestational diabetic mothers.Conclusion: Maternal diabetes significantly affects neonatal outcomes, with frequent immediate complications including respiratory distress, hypoglycemia, hyperbilirubinemia, and hypocalcemia. Close monitoring and effective glycemic control during pregnancy are essential to minimize risks for infants of diabetic mothers. J Med Coll Women Hosp.2026; 22(1): 53-59